f(-3) means x=-3 so substitute all x's for -3
So, f(-3)=-3^2+2(-4) ?
yes right remember coefficient is also negative so \[\huge\rm -(-3)^2+2(-3)\] now solve
hmm no (-3)^2 =?
(-3)^2 is same as -3 times -3
yes right so-(9)+2(-3) = ?
I got -15.
Would that be my final answer?
Okay, would you mind helping me with just one more?
If f(x)=x-3 and g(x)=2x-4, find (f+g)(x).
I tried working this one out and got 3x-7. Which I don't think is right.
just one question how did you get 3x :=)
I have no idea honestly. Haha
so how did you get 3x-7 ?
At the end how it has f+g and then x. I think that's how I got the x. Can you help?
(f+g)(x) means add both function f(x) and g(x) so f(x) + g(x)
so replace f(X) with x-3 and f(x) with 2x-4 and then combine like terms (x-3)+(2x-4)
Wouldn't you add the x to 2x and it becomes 3x?
yes right that's what i was asking
Thank you, so now the -3 and -4¿
yes right -3-4 are like terms
Would it be -7?
Ohh, would my answer actually be 3x-7?
Thank you so much for the help!